Introductory Modal Logic - Konyndyk, Kenneth J., Jr. (Notre Dame : University of Notre Dame Press, 1986)
Modal logic, developed as an extension of classical propositional logic and first-order quantification theory, integrates the notions of possibility and necessity and necessary implication. Arguments whose understanding depends on some fundamental knowledge of modal logic have always been important in philosophy of religion, metaphysics, and epistemology. Moreover, modal logic has become increasingly important with the use of the concept of "possible worlds" in these areas. Introductory Modal Logic fills the need for a basic text on modal logic, accessible to students of elementary symbolic logic. Kenneth Konyndyk presents a natural deduction treatment of propositional modal logic and quantified modal logic, historical information about its development, and discussions of the philosophical issues raised by modal logic. Characterized by clear and concrete explanations, appropriate examples, and varied and challenging exercises, Introductory Modal Logic makes both modal logic and the possible-worlds metaphysics readily available to the introductory level student.
Cover -- Half title -- Title page -- Copyright -- CONTENTS -- PREFACE -- INTRODUCTION -- 1. PROPOSITIONAL LOGIC -- 2. PROPOSITIONAL MODAL LOGIC -- 3: QUANTIFICATION -- 4. QUANTIFIED MODAL LOGIC -- APPENDIX I -- APPENDIX II -- APPENDIX III -- NOTES -- BIBLIOGRAPHY
Print version record.
JSTOR
Keywords: Modality (Logic); Modalité (Logique); PHILOSOPHY / Logic; Electronic books